Practical Network Scanning : Capture network vulnerabilities using standard tools such as Nmap and Nessus. - Cox, Jacob (Packt Publishing, 2018)
Network administrators use network scanning tools to build a network inventory and to perform security audits by examining active hosts on a network with the help of IP address ranges. The same principles can also be used in cyber attacks to find weaknesses in a system. This book will help you not only find flaws but also strengthen the ...